Non-Thermal Plasma: A Promising Technology for the Germination Enhancement of Radish (Raphanus sativus) and Carrot (Daucus carota sativus L.). (4th March 2023) - Guragain, Rajesh Prakash; Baniya, Hom Bahadur; Shrestha, Bikash; Guragain, Deepesh Prakash; Subedi, Deepak Prasad
Abstract : Cold plasma is an innovative and promising technology that is developing in a variety of fields, and recently it has been getting a lot of attention in the agricultural industry. The influence of cold atmospheric pressure plasma (CAPP) exposure on germination parameters and vigor of radish ( Raphanus sativus ) and carrot ( Daucus carota sativus L.) seeds was investigated in the present study. A custom-designed plasma driver utilizing 11.32 kV rms and 50 Hz was used for the generation of the discharge. Seeds were treated using a dielectric barrier discharge (DBD) in an argon atmosphere at exposure periods of 1–4 minutes. The estimate of plasma parameters was done using optical emission spectroscopy and electrical measurements. Germination-related measures such as the final germination percentage, germination index, germination value, coefficient of velocity of germination, vigor index, and chlorophyll content were all improved in the case of CAPP-treated seeds as compared to control seeds. Similarly, CAPP treatment changed the in vitro radical scavenging capabilities, total phenolic, and total flavonoid levels of the seedlings. Our results indicated that the seeds being treated by CAPP for 3 minutes seemed to have a favorable impact on seed germination and sprouting development.